Sinonasal adenocarcinoma: clinical study of nine cases in Taiwan. - Lee C; Liu T; Hsu C; Chen Y (Acta Oto-Laryngologica, 2002)
Objective-Sinonasal adenocarcinoma is an uncommon disease in Taiwan. This paper presents details of the management and outcome of the disease. Material and methods-The medical records of patients with sinonasal adenocarcinoma who presented to the Department of Otolaryngology, National Taiwan University Hospital between 1983 and 2002 were retrospectively reviewed. Tumors were staged based on the American Joint Committee of Cancer staging criteria. The series included 5 males and 4 females (mean age 51 years; range 28-75 years). Results-No association between sinonasal adenocarcinoma and occupations such as furniture making, wood working or textile working was found. Epistaxis and nasal obstruction were the most common symptoms. Metastasis to bone or liver was found initially at diagnosis in two cases. Treatment was given according to the tumor stage, the clinical condition of the patient and the patient's wishes: two received combined treatment comprising wide surgical resection and radiotherapy, two received radiotherapy only, one received wide surgical resection only and four received no treatment. At a mean follow-up of 30 months (range 2-68 months), 2 patients were free from the disease and 1 was alive with the disease. Six cases died of the disease. Advanced-stage disease was associated with a poor prognosis. Early-stage disease, a well-differentiated histologic type and surgical resection combined with radiotherapy were associated with a favorable result. Conclusion-Sinonasal adenocarcinoma has a low incidence in the general population in Taiwan. However, prognosis is poor owing to delayed diagnosis and the consequent advanced stage of the disease.